2016
DOI: 10.1038/srep35894
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and inhibition of Trypanosoma brucei hypoxanthine–guanine phosphoribosyltransferase

Abstract: Human African Trypanosomiasis (HAT) is a life-threatening infectious disease caused by the protozoan parasite, Trypanosoma brucei (Tbr). Due to the debilitating side effects of the current therapeutics and the emergence of resistance to these drugs, new medications for this disease need to be developed. One potential new drug target is 6-oxopurine phosphoribosyltransferase (PRT), an enzyme central to the purine salvage pathway and whose activity is critical for the production of the nucleotides (GMP and IMP) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…This binding mode is commonly observed for the nucleoside monophosphates when in complex with the 6‐oxopurine PRTs. However, it has also been observed in other crystal structures that the 5′‐phosphate group can be located outside the 5′‐phosphate binding pocket and protruding out from the active site (Fig. ).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…This binding mode is commonly observed for the nucleoside monophosphates when in complex with the 6‐oxopurine PRTs. However, it has also been observed in other crystal structures that the 5′‐phosphate group can be located outside the 5′‐phosphate binding pocket and protruding out from the active site (Fig. ).…”
Section: Resultsmentioning
confidence: 57%
“…The quaternary structures of 6‐oxopurine PRTs from several organisms have previously been determined and have been shown to be either tetramers or dimers . For example, human HGPRT and Pf HGXPRT are tetrameric, T. cruzi HGPRT can exist as either a dimer or tetramer , while Tbr HGPRT and Tsu HGXPRT are dimers. Tbr HGXPRT was analysed by SEC‐MALLS (size exclusion chromatography multi‐angle laser light scattering) which showed that the major component has a molecular weight of 53.9 ± 0.3 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two loops, loop II and loop IV, are observed to make a network of interactions with terminal phosphate moieties of PRPP. The PRPP binding pocket is highly conserved among all Type-1 PRTases with a canonical DD motif, which stabilizes the co-factor Mg 2+ ion together with the ribose moiety of PRPP [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…19 Nucleoside phosphonates bearing guanine or hypoxanthine as the nucleobase are effective inhibitors of Pf HGXPRT and Pv HGPRT. They also inhibit the bacterial 6-oxopurine PRTases from Mycobacterium tuberculosis, 20 Escherichia coli, 21,22 and the HGPRT found in the parasite Trypanosoma brucei 23 . A variety of different structural analogues of these phosphonate inhibitors have been synthesised, including the single chain ANPs, the ANbPs, the aza-ANPs, the pyrrolidine nucleoside phosphonates, the pyrrolidine nucleoside bisphosphonates and the acylic immucillin phosphonates.…”
Section: Introductionmentioning
confidence: 99%